Could bacterial associations determine the success of weevil species?. (6th August 2020) - Morera‐Margarit, Pilar; Pope, Tom W.; Mitchell, Carolyn; Karley, Alison J.
Abstract: The weevil superfamily Curculionoidea is the largest insect group and so the largest animal group on earth. This taxon includes species which represent an important threat to many economically important crops and, therefore, pose a risk to agriculture and food security. Insect–bacteria associations have been recognised to provide the insect host with many benefits, such as ensuring the acquisition of essential nutrients or protecting the host from natural enemies. The role of bacteria associations within the weevil superfamily remains nonetheless understudied in comparison with other insect taxa. This review draws together existing knowledge on the influence of bacteria associated with weevils known to be agricultural pest species. The implications of these weevil–bacterial associations in determining pest status and their relevance to targeted pest management interventions are discussed. Specific consideration is given to the role of bacteria in cuticle formation, flight activity, reproduction manipulation and adaptation to different environments and food sources. Abstract :